2016
DOI: 10.2105/ajph.2016.303111
|View full text |Cite
|
Sign up to set email alerts
|

Educational Interventions to Promote Healthy Nutrition and Physical Activity Among Older Chinese Americans: A Cluster-Randomized Trial

Abstract: In-language print materials, alone and combined with lectures, increased nutrition and physical activity knowledge and behaviors among older Chinese Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Baseline rates of knowledge and self-reported adherence to recommendations for fruit and vegetable intake were low among Vietnamese Americans; this finding is consistent with published studies of other racial/ethnic groups (25,26). A study published almost 25 years ago reported that Vietnamese Americans in California consumed only 3.5 servings of fruits and vegetables per day (8).…”
Section: Discussionsupporting
confidence: 86%
“…Baseline rates of knowledge and self-reported adherence to recommendations for fruit and vegetable intake were low among Vietnamese Americans; this finding is consistent with published studies of other racial/ethnic groups (25,26). A study published almost 25 years ago reported that Vietnamese Americans in California consumed only 3.5 servings of fruits and vegetables per day (8).…”
Section: Discussionsupporting
confidence: 86%
“…In previously published studies, combined home-based volunteerled physical activity and nutrition programs have been shown to be effective in terms of changing physical activity and nutrition-based behavior. [7][8][9] These studies reported a significant increase in carrying out strength exercises and moderate intensity sport participation. It is, however, noteworthy that these studies focused on nutritional behavior as consumption of fruit and vegetables, fat avoidance, fiber intake, 8 and adherence to fruit and vegetable intake recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In previously published studies, combined home‐based volunteer‐led physical activity and nutrition programs have been shown to be effective in terms of changing physical activity and nutrition‐based behavior . These studies reported a significant increase in carrying out strength exercises and moderate intensity sport participation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations